2020
DOI: 10.3390/healthcare8040483
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Elective Neurosurgery at a German University Hospital during the First Wave of COVID-19

Abstract: Background: Patients’ fear of the coronavirus disease 2019 (COVID-19) may delay inevitable treatment, putting potential benefits at risk. This single-center retrospective study aims to analyze temporal relationships of the first wave of the COVID-19 pandemic in Germany with the number of patients who sought and received elective neurosurgical treatment at a German university hospital. Methods: Daily outpatient numbers (ON) and elective procedures (EP) were recorded at our department between 1 January 2020 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…1 ). These included 59 peer-reviewed studies (Arndt et al 2022 ; Balakirski et al 2022 ; Balk et al 2022 ; Bartella et al 2021 ; Beller et al 2022 ; Bollmann et al 2021 ; Brunner et al 2020 ; Buntzel et al 2020 , 2021 ; Dienemann et al 2021 ; Diers et al 2021 , 2022 ; Donath et al 2021 ; Eckford et al 2021 ; Erdmann et al 2021 , 2022 ; Fauser et al 2022 ; Gremke et al 2022 ; Griewing et al 2022a , b ; Gschnell et al 2021 ; Haier et al 2022a , b , c ; Hajek et al 2021 ; Harke et al 2020 , 2022 ; Heimes et al 2021 ; Holzel et al 2022 ; Hunger et al 2022 ; Jacob et al 2021 , 2022 ; Jördens et al 2021 ; Justenhoven and Rieger 2022 ; Kaltofen et al 2022 ; Kapsner et al 2020 ; Kirchberg et al 2021 ; Kleemann et al 2022 ; Kourtidis et al 2022 ; Kuhlen et al 2020 ; Matuschek et al 2020 ; Medenwald et al 2022 ; Micek et al 2022 ; Michalowsky et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Riemann et al 2021 ; Rupa et al 2020 ; Schuz et al 2022 ; Stang et al 2020 ; Stos et al 2020 ; Struck et al 2022 ; Teuscher et al 2022 ; Voigtlander et al 2021 ; Vu et al 2022 ; Walter et al 2021 , ...…”
Section: Resultsunclassified
“…1 ). These included 59 peer-reviewed studies (Arndt et al 2022 ; Balakirski et al 2022 ; Balk et al 2022 ; Bartella et al 2021 ; Beller et al 2022 ; Bollmann et al 2021 ; Brunner et al 2020 ; Buntzel et al 2020 , 2021 ; Dienemann et al 2021 ; Diers et al 2021 , 2022 ; Donath et al 2021 ; Eckford et al 2021 ; Erdmann et al 2021 , 2022 ; Fauser et al 2022 ; Gremke et al 2022 ; Griewing et al 2022a , b ; Gschnell et al 2021 ; Haier et al 2022a , b , c ; Hajek et al 2021 ; Harke et al 2020 , 2022 ; Heimes et al 2021 ; Holzel et al 2022 ; Hunger et al 2022 ; Jacob et al 2021 , 2022 ; Jördens et al 2021 ; Justenhoven and Rieger 2022 ; Kaltofen et al 2022 ; Kapsner et al 2020 ; Kirchberg et al 2021 ; Kleemann et al 2022 ; Kourtidis et al 2022 ; Kuhlen et al 2020 ; Matuschek et al 2020 ; Medenwald et al 2022 ; Micek et al 2022 ; Michalowsky et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Riemann et al 2021 ; Rupa et al 2020 ; Schuz et al 2022 ; Stang et al 2020 ; Stos et al 2020 ; Struck et al 2022 ; Teuscher et al 2022 ; Voigtlander et al 2021 ; Vu et al 2022 ; Walter et al 2021 , ...…”
Section: Resultsunclassified
“…In the beginning of 2020, the coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) [ 4 ], brought about a demand to quickly reallocate healthcare resources [ 5 , 6 ]. Subsequently, we and other neurosurgeons [ 7 , 8 ] were concerned about the possibility of an involuntary triage of neurosurgical patients due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on protocols or surgical recommendations for neurosurgery in patients with COVID-19. 1 2 4 5 6 7) Lee et al 4) developed a clinical pathway for patients indicated for emergency brain surgery from the emergency room, applied it to the actual clinical field, and published it. These studies are thought to enable a sufficient response in a wide range of outbreaks of not only COVID-19, but also other various respiratory diseases that may occur in the future.…”
mentioning
confidence: 99%